Refugees and civic stratification: The "Asian rejection" hypothesis and its implications for protection claimants in Hong Kong. (June 2017) - Lai, Ada Pui Yim; Kennedy, Kerry J
Hong Kong is not a signatory to the 1951 Convention Relating to the Status of Refugees yet, it has historically attracted refugees from Mainland China and, in the 1970s, from Vietnam. Today, there is a refugee flow from different parts of Southeast Asia. This paper highlights the plight of refugees in an environment where there are no legal frameworks for managing refugees, where there is a deliberate policy of not settling refugees, irrespective of the validity of their claims, and where minimal support is provided for claimants waiting to have their claims assessed. Civic stratification is advanced as a theoretical framework for understanding the status of refugees in Hong Kong and the extent to which resistance is possible within this framework is demonstrated.